A Proposal of Rewards-Linked Performance Development System: A Case Study of PT MNO - Gumilang, Danang Muchammad; Anggoro, Yudo (Graduate Program Magister Manajemen Pendidikan, 2025)
This study highlights the gap between formal performance development values ​​and hierarchical work culture in emerging market FMCG companies, specifically in PT MNO, Indonesia. This qualitative research proposes a reward-integrated Performance Development System (PDS) that aligns with agile transformation goals and cultural realities. Data from in-depth interviews, surveys, HR documents, and performance reports indicate that the existing PDS is ambiguous, disconnected from career development, bureaucratic, and inconsistent with rewards. Cultural aspirations such as agility and autonomy are hampered by high power distance and collectivist norms, reducing clarity and trust. Therefore, a new PDS model that is culturally responsive and behaviorally aligned is developed. The model includes shared goal setting, continuous feedback, transparent communication of performance and reward expectations, and competency-based achievement tied to financial incentives and career mobility. This approach is expected to increase employee engagement, fairness, system adoption, and alignment with business agility. This study makes a significant contribution as the first adaptive PDS blueprint that integrates a transparent dual-track reward mechanism while bridging the barriers of hierarchical culture with agile performance demands in emerging markets. It offers practical guidance for HR leaders and transformation architects.